2022
DOI: 10.1007/s00198-021-06174-0
|View full text |Cite
|
Sign up to set email alerts
|

Romosozumab and antiresorptive treatment: the importance of treatment sequence

Abstract: To evaluate whether treatment sequence affects romosozumab response, this analysis reviewed studies where romosozumab was administered before or following an antiresorptive (alendronate or denosumab). Initial treatment with romosozumab followed by an antiresorptive resulted in larger increases in bone mineral density of both hip and spine compared with the reverse sequence. Introduction Teriparatide followed by an antiresorptive increases bone mineral density (BMD) more than using an antiresorptive first. To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 59 publications
0
22
0
5
Order By: Relevance
“…Lower BMD gains were also noted when romosozumab treatment was preceded by denosumab. 32 Taken together, romosozumab used before rather than after alendronate leads to more significant bone mineral density increases and BMD responder rates. Therefore, with BMD gain with treatment being an essential indicator for bone strength and reduction in fracture risk, using romosozumab before an antiresorptive agent might be the ideal sequence for treatment.…”
Section: Switching High-risk Patients Previously On Bisphosphonates T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Lower BMD gains were also noted when romosozumab treatment was preceded by denosumab. 32 Taken together, romosozumab used before rather than after alendronate leads to more significant bone mineral density increases and BMD responder rates. Therefore, with BMD gain with treatment being an essential indicator for bone strength and reduction in fracture risk, using romosozumab before an antiresorptive agent might be the ideal sequence for treatment.…”
Section: Switching High-risk Patients Previously On Bisphosphonates T...mentioning
confidence: 99%
“…Therefore, with BMD gain with treatment being an essential indicator for bone strength and reduction in fracture risk, using romosozumab before an antiresorptive agent might be the ideal sequence for treatment. 32 …”
Section: Switching High-risk Patients Previously On Bisphosphonates T...mentioning
confidence: 99%
“…45,46 The ARCH trial demonstrated a small increase in the incidence of cardiovascular events in the romosozumab arm, which was not seen in other trials. 47 More supporting data are required, but romosozumab is currently not recommended for patients with a high risk of myocardial infarction or stroke. Other common adverse effects include injection-site reactions.…”
Section: Romosozumabmentioning
confidence: 99%
“…More research is required to determine if the gains in bone density also correlate with a reduced fracture risk in these patients. 47 Given this evidence, for some treatment-naïve patients who present with severe osteoporosis (T-score less than -3.0) following a fracture, the option of first-line treatment with an anabolic drug such as romosozumab should be discussed with the patient. However, this is not a PBS-listed indication.…”
Section: Sequential Treatment With First-line Anabolicsmentioning
confidence: 99%
“…In contrast, transition to romosozumab resulted in a 10% gain at the spine and 3% gain at hip sites (96). Some studies suggest that anabolic agents produce smaller gains in BMD when administered after an anti-resorptive agent compared with their use in treatment-naïve patients (96,97). Such analyses need to factor in the earlier BMD gains from anti-resorptive use when assessing the total BMD benefit.…”
Section: Treatment Ordermentioning
confidence: 99%